EFFORTS TO ENHANCE ENGLISH LEARNING MOTIVATION USING THE CONTEXTUAL TEACHING LEARNING (CTL) METHOD IN CLASS X-2 AT SMAN PAKUSARI - Anggraeni, Siska; Nurkamilah; Dewi, Rita Sinta (Transpublika Publisher, 2023)
This Classroom Action Research (CAR) aims to describe the English learning outcomes of Grade X-2 students at Pakusari High School in Jember before and after applying the contextual teaching and learning (CTL) method. The study involved 36 students in the academic year 2022/2023. The analysis of the data revealed that the English learning motivation of Grade X-2 students at Pakusari High School prior to implementing the contextual teaching and learning method was as follows: 6% of the students had very high motivation; 31% had high motivation; 39% had moderate motivation; and 25% had low motivation. Conversely, after implementing the contextual teaching and learning method, there was an improvement in English learning motivation: 14% of the students had very high motivation; 67% had high motivation; 17% had moderate motivation; and 3% had low motivation.